Structural investigations of molecular solutes within nanostructured ionic liquids. Issue 20 (13th May 2020) - Yalcin, Dilek; Welsh, Ivan D.; Matthewman, Emma L.; Jun, Seongmin Paul; Mckeever-Willis, Mikkaila; Gritcan, Iana; Greaves, Tamar L.; Weber, Cameron C.
Abstract : Amphiphilic nanostructures of ionic liquids are retained to high solute concentrations and the partitioning of solutes within these nanostructures can be rationally influenced by ion selection. Abstract : Ionic liquids (ILs) containing sufficiently long alkyl chains form amphiphilic nanostructures with well-defined polar and non-polar domains. Here we have explored the robustness of these amphiphilic nanostructures to added solutes and gained insight into how the nature of the solute and IL ions affect the partitioning of these solutes within the nanostructured domains of ILs. To achieve this, small angle X-ray scattering (SAXS) investigations were performed and discussed for mixtures of 9 different molecular compounds with 6 different ILs containing imidazolium cations. The amphiphilic nanostructure of ILs persisted to high solute concentrations, over 50 mol% of added solute for most 1-butyl-3-methylimidazolium ILs and above 80 mol% for most 1-decyl-3-methylimidazolium ILs. Solute partitioning within these domains was found to be controlled by the inherent polarity and size of the solute, as well as specific interactions between the solute and IL ions, with SAXS results corroborated with IR spectroscopy and molecular dynamics simulations. Molecular dynamics simulations also revealed the ability to induce π + –π + stacking between imidazolium cations through the use of these added molecular compounds. Collectively, these results provide scope for the selection of IL ions to rationally influence and control the partitioning behaviour of given solutes within the amphiphilic nanostructure of ILs.